The role of magnetic fields in the formation and propagation of hadronic microquasars jets - Paspaliaris, E.-D. S.; Smponias, T.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2019)
In the present work, we examine the role of the magnetic field (MF), which causes a rather pronounced confinement of the jets at microquasars. Due to radial Lorentz forces acting on the jet’s matter towards the jet’s axis, the outgoing flux is collimated along the same axis and vertically to the compact object. Alternatively, a rotating central object may drag the surrounding MF into collimation around the produced jet. In such objects, jet emerges from each side of the accretion disc. These jets operate as cosmic engines, capable of accelerating particles on very high energies (~10^2 TeV) and consist sources of high energy neutrinos and gamma rays. We also examine the role of the MF, which causes to a rather pronounced jet confinement. Our aim is to investigate and model its role on various physical observables of the jet, by simulating the jet’s flow and derive 2D and 3D visualizations and furthermore examine its effect on the neutrino emissivity.